If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 5p = 6p Solving 7 + 5p = 6p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-6p' to each side of the equation. 7 + 5p + -6p = 6p + -6p Combine like terms: 5p + -6p = -1p 7 + -1p = 6p + -6p Combine like terms: 6p + -6p = 0 7 + -1p = 0 Add '-7' to each side of the equation. 7 + -7 + -1p = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1p = 0 + -7 -1p = 0 + -7 Combine like terms: 0 + -7 = -7 -1p = -7 Divide each side by '-1'. p = 7 Simplifying p = 7
| 7+5(2x+3)-9= | | 3x+8x-2=108 | | 27=3u-15 | | 10m+8m=108 | | -12.72+(-1.008)-(-4.3)+9.17= | | 7w-11w=8 | | -14-(-50)=x/8 | | q+358=435 | | log2/log(1/4) | | 3v-13=35 | | 2x+28=4x+1 | | 13+7.1x=5(1.5x+2) | | 2-2x=-6+2x | | 5x-17=11x-11 | | 3x-79=-11x+131 | | 62=5u+12 | | -12+a=18 | | 0.42a=0.08a+0.75 | | X+14=22.6 | | 6-1/3x-3=-1/2x | | 42x^2+x=1 | | 3j-5=13 | | 1/4*12m | | 8x^2-6x-12=0 | | (143)(y)=6 | | 0.6x+11=0.8x-1 | | 9+2t=17 | | 9y-85=7(4+y) | | 14u=24+8u | | 4(x+3y+5)+2(x-1)= | | Y=2x+24x-16 | | 143xy=6 |